2021
DOI: 10.1002/anie.202015679
|View full text |Cite
|
Sign up to set email alerts
|

A Robust PtNi Nanoframe/N‐Doped Graphene Aerogel Electrocatalyst with Both High Activity and Stability

Abstract: Insufficient catalytic activity and stability and high cost are the barriers for Pt‐based electrocatalysts in wide practical applications. Herein, a hierarchically porous PtNi nanoframe/N‐doped graphene aerogel (PtNiNF‐NGA) electrocatalyst with outstanding performance toward methanol oxidation reaction (MOR) in acid electrolyte has been developed via facile tert‐butanol‐assisted structure reconfiguration. The ensemble of high‐alloying‐degree‐modulated electronic structure and correspondingly the optimum MOR re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 63 publications
2
76
0
Order By: Relevance
“…Until now, many efforts have been made on the adequate exposure of all the Pt species in the entire electrode, the activity modulation of each active site, and the stabilization of the active sites during the electrocatalysis. [15] Due to the large surface area, an interconnected 3D network, hierarchical porosity, and the feasibility of structure and composition design of their backbones, aerogels have drawn growing attention, emerged as good candidates for electrocatalysts or their supports, [16][17][18][19][20][21][22][23][24] and shown remarkable electrocatalytic performance in HER. [25] However, the aerogel-based HER electrocatalysts are still limited and mainly restricted to PtAu and AuRh noble-metal backbone aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many efforts have been made on the adequate exposure of all the Pt species in the entire electrode, the activity modulation of each active site, and the stabilization of the active sites during the electrocatalysis. [15] Due to the large surface area, an interconnected 3D network, hierarchical porosity, and the feasibility of structure and composition design of their backbones, aerogels have drawn growing attention, emerged as good candidates for electrocatalysts or their supports, [16][17][18][19][20][21][22][23][24] and shown remarkable electrocatalytic performance in HER. [25] However, the aerogel-based HER electrocatalysts are still limited and mainly restricted to PtAu and AuRh noble-metal backbone aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…Among reported noble-based catalysts, those based on the Pt metal are regarded as the star electrocatalysts for the AORs in terms of their oxidation overpotentials and Tafel slopes. [12,13] Notably, their alloys with other metals (e.g., Ru, Ni, Co, Pd, Rh, and Au) exhibit strong adsorption capability toward OH species or a so-called bifunctional mechanism, leading to improved AOR performance. [14][15][16][17] On the other hand, the serious poisoning effect of the carbonaceous intermediates (especially CO) hinders dramatically the activity of the used catalysts (especially the Pt catalysts) and eventually leads to much reduced conversion efficiencies of the AORs.…”
mentioning
confidence: 99%
“…The binding energies (BEs) of Pt 4f 7/2 in Pt 55.1 Bi 44.9 , Pt 51.3 Bi 46.8 Au 1.9 , Pt 53.1 Bi 43.4 Au 3.5 , and Pt 50.9 Bi 43.3 Au 5.8 were found to be 70.56, 70.61, 70.65, and 70.83 eV, respectively, that shifted negatively by 0.84, 0.79, 0.75 and 0.57 eV compared to that of the commercial Pt black (Pt 4f 7/2 : 71.4 eV), showing the existence of strong electronic effects and downshift in the d‐band center of Pt. [ 51–54 ] The valence band spectra (Figure 2d) confirmed that the d‐band center of Pt in the intermetallic Pt 55.1 Bi 44.9 (−3.956 eV) and Pt 53.1 Bi 43.4 Au 3.5 (−3.942 eV) downshifted relative to pure Pt black (−3.774 eV). The downward movement of the d‐band center of Pt weakened the binding strength of the intermediates on the Pt active sites, expedited the reaction kinetics and then dramatically improved the catalytic performances in electrocatalysis.…”
Section: Resultsmentioning
confidence: 72%